Umbilical Vein Calcification Associated with Double-Lumen Catheter Malpositioning in an Extremely Low-Birth-Weight Infant - Takuya Yamamoto; Shigeo Iijima (Pediatric Reports, 2024)
Umbilical venous (UV) catheters (UVCs) are commonly used in severely ill neonates. Complications associated with UVC often result from an inappropriate UVC position. Calcification of the UV, a rare complication, was observed in an extremely low-birth-weight infant born at 23 weeks of gestation. After birth, the infant experienced respiratory and circulatory dysfunction, followed by disseminated intravascular coagulation (DIC). A UVC was inserted, and circulatory agonists and blood transfusions were administered, as well as a calcium gluconate infusion for hypocalcemia and hyperkalemia. Ten days after birth, calcification was detected in the UV, likely due to a tunica intima injury caused by UVC, a hypercoagulable state due to DIC, and a high-dose calcium gluconate infusion. Additionally, proximal port malpositioning of the double-lumen catheter might have contributed to calcification within the UV. To prevent such complications, real-time ultrasound confirmation with agitated saline contrast during UVC placement is recommended; in the absence of the facility or skills for ultrasonography, X-rays should be performed in the lateral and anteroposterior views. Furthermore, when using multi-lumen catheters, physicians should not only verify the tip position but also ensure proper placement of proximal ports and carefully select medications administered through the ports.